2D Materials: The Role of Graphene and Other 2D Materials in Solar Photovoltaics (Adv. Mater. 1/2019). Issue 1 (3rd January 2019) - Das, Sonali; Pandey, Deepak; Thomas, Jayan; Roy, Tania
Abstract : 2D materials hold immense potential for future, lightweight, flexible solar cells. In article number1802722, Jayan Thomas, Tania Roy, and co‐workers describe recent progress made with graphene and other 2D materials for silicon, organic, and perovskite solar photovoltaics. They also present an outlook for meeting the challenges and requirements for 2D‐materials‐based next‐generation solar photovoltaics at low cost and high production rate.